2008
DOI: 10.4103/0250-474x.45405
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and evaluation of tramadol hydrochloride rectal suppositories

Abstract: Rectal suppositories of tramadol hydrochloride were prepared using different bases and polymers like PEG, cocoa butter, agar and the effect of different additives on in vitro release of tramadol hydrochloride was studied. The agar-based suppositories were non-disintegrating/non-dissolving, whereas PEGs were disintegrating/dissolving and cocoa butter were melting suppositories. All the prepared suppositories were evaluated for various physical parameters like weight variation, drug content and hardness. The PEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 4 publications
1
19
0
Order By: Relevance
“…As PEGs might be slightly irritant in children (EMA, 2006), no other surfactants were added to avoid problems with local tolerability or early expulsion of the form. A mixture of two PEGs, one of low and the other of high molecular weight, is commonly used for conventional rapid-release suppositories (Saleem et al, 2008). Different ratios of PEG 1500/4000 were tested; 80% PEG 1500 plus 20% PEG 4000 (melting point >50 °C as per the TPP) was selected (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As PEGs might be slightly irritant in children (EMA, 2006), no other surfactants were added to avoid problems with local tolerability or early expulsion of the form. A mixture of two PEGs, one of low and the other of high molecular weight, is commonly used for conventional rapid-release suppositories (Saleem et al, 2008). Different ratios of PEG 1500/4000 were tested; 80% PEG 1500 plus 20% PEG 4000 (melting point >50 °C as per the TPP) was selected (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Liquid suppositories are also reported by PVP applications [ 112 ]. Saleem et al reported the use of PVP along with agar for developing sustained release rectal suppositories of tramadol hydrochloride [ 119 ].…”
Section: Pharmaceutical and Other Applicationsmentioning
confidence: 99%
“…Hardness test was carried out to determine the tensile strength and ability of the suppositories to withstand the hazards of packing and transportation using Monsanto hardness tester (Veego Scientific, Model HT-1). [21] Liquefaction time Liquefaction time was measured using a pipette having a broad opening on one side and a narrow opening on the other. Suppository was pushed inside in such a way that the broad end side of suppository to reach to the narrow end of pipette.…”
Section: Weight Variation Testmentioning
confidence: 99%